Urinary miR‐3137 and miR‐4270 as potential biomarkers for diabetic kidney disease. Issue 12 (1st September 2020) - Li, Xiaoyu; Xu, Rong; Liu, Xiangyang; Xu, Linxin; Xue, Mei; Cheng, Ying; Li, Ting; Yu, Xiaochen; Wang, Yue; Li, Chunjun; Sun, Bei; Chen, Liming
Abstract: Background: As one of the most prevalent diagnostic indicators of diabetic kidney disease (DKD), albumin‐to‐creatinine ratio (ACR) shows considerably limited predictive power in clinical application. We analyzed microarray expression profiling of urine to seek for differentially expressed miRNAs for potential biomarkers of DKD. Methods: Urine samples from type 2 diabetes mellitus (T2DM) patients with (30 mg/g < ACR < 300 mg/g, DKD group) or without DKD (ACR < 30 mg/g, DM group) were collected for miRNA microarray analysis. The differentially expressed miRNAs were screened by bioinformatics analysis and validated by quantitative real‐time PCR. Target genes of differentially expressed miRNAs were predicted in miRDB, Targetscan, and microRNA.org databases. We also conducted the Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) signaling pathways analysis to explore for potential mechanisms in DKD. Results: Nine miRNAs were down‐regulated and seventeen miRNAs were up‐regulated in DKD group, compared to DM group. The levels of miR‐3137 and miR‐4270 in DKD group were 0.670 ± 0.505 and 2.116 ± 1.762 times than those in DM group, respectively, showing great significance. A total of 1076 target genes were simultaneously predicted by miRDB, Targetscan, and microRNA.org databases. According to the GO analysis results, disorders of endomembrane system may be one of the major pathological changes in DKD. In addition, Rap 1 signaling pathway is also altered obviously in DKD, discovered by the KEGG analysis. Conclusion: MiR‐3137 and miR‐4270 show the potential for urinary biomarkers of DKD. The pathological changes of DKD may be related to disorders of endomembrane system and alternation of Rap1 signaling pathway. Abstract : The levels of miR‐3137 and miR‐4270 in urine of DKD patients were 0.670 ± 0.505 and 2.116 ± 1.762 times than those in DM group, showing the potential for urinary biomarkers of DKD. The pathological changes of DKD may be related to disorders of endomembrane system and alternation of Rap1 signaling pathway.